Serum γ-glutamyltransferase: new insights about an old enzyme. Issue 11 (13th October 2009) - Lee, D-H; Jacobs, D R
Abstract : In recent prospective studies, serum γ-glutamyltransferase (GGT) within its normal range predicts various diseases with diverse pathophysiological processes. At present, the prevailing interpretation is that serum GGT is a marker of fatty liver or oxidative stress. However, serum GGT may predict many diseases as a cumulative biomarker of various environmental chemicals; cellular GGT is prerequisite for metabolism of glutathione (GSH) conjugates and GSH is a critical biomolecule for conjugation diverse chemicals. Supporting this concept, serum GGT within its normal range had clear dose–response associations with a variety of chemicals such as lead, cadmium, organochlorine pesticides, and dioxin. This idea is only at a beginning stage. If the associations of serum GGT with environmental chemicals were confirmed, it could have an enormous impact on public health because it would indicate that exposure to mixed chemicals at very low levels may not actually be safe.